2007
DOI: 10.2460/javma.230.7.1011
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day variability of blood glucose concentration curves generated at home in cats with diabetes mellitus

Abstract: Considerable day-to-day variability was detected in BGCs generated at home. Cats with good glycemic control may have more reproducible curves generated during blood collection at home than cats with poorer control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
2
27
0
4
Order By: Relevance
“…[34][35][36]85 U s e o f b l o o d g l u c o s e c u r v e s BGCs can be very useful in the assessment of feline DM ( Figures 4 and 5), although they have limitations and there is considerable day-to-day variation in results, especially in cats with poor glycaemic control. 96 Compared with home BGCs, those performed in-clinic may either over-or underestimate glycaemic control (Figure 4), perhaps reflecting natural daily variation but also the influence of stress, variations in insulin dose and possibly variable food intake. 92 In-clinic BGCs should, therefore, be interpreted with great caution and in the light of the clinical data.…”
Section: Home Monitoring Of Blood Glucosementioning
confidence: 99%
“…[34][35][36]85 U s e o f b l o o d g l u c o s e c u r v e s BGCs can be very useful in the assessment of feline DM ( Figures 4 and 5), although they have limitations and there is considerable day-to-day variation in results, especially in cats with poor glycaemic control. 96 Compared with home BGCs, those performed in-clinic may either over-or underestimate glycaemic control (Figure 4), perhaps reflecting natural daily variation but also the influence of stress, variations in insulin dose and possibly variable food intake. 92 In-clinic BGCs should, therefore, be interpreted with great caution and in the light of the clinical data.…”
Section: Home Monitoring Of Blood Glucosementioning
confidence: 99%
“…Cats with diabetes rarely achieve the levels of glycemic control considered satisfactory because of prolonged hyperglycemia that can last 20 to 24 hours after a single meal, and variability of the blood glucose concentration during the day (Rand 2006). Recent studies reported the considerable day-to-day variability in BGCs in diabetic cats, even when factors such as insulin dose and meal size remain constant and the cat is at home in a stress-free environment (Alt et al 2007). Causes of persistent day-to-day variability in glucose concentration include rate of insulin absorption when different sites are used, variation in the length of insulin activity, variation in insulin sensitivity among individuals, and variation of residual beta-cell function.…”
Section: Discussionmentioning
confidence: 96%
“…The theoretical advantages over performing the same procedure at the hospital include increased reliability of the results since there is no significant change of daily routine (feeding, exercise) or interference by the stress of hospitalization, and the reduced cost (Alt et al, 2007;Ford and Lynch, 2013). Serial blood glucose curves at the hospital suffer from day to day variation in both diabetic dogs and cats; their repeatability, even when performed on consecutive days, is that low that may result in opposite recommendations for adjustment of insulin dose (Alt et al, 2007;Ford and Lynch, 2013). However, even at the home environment day to day variation is also expected, although it is less problematic in well regulated diabetic animals (Alt et al, 2007).…”
Section: Home Monitoring Of Blood Glucose Concentrations By the Ownermentioning
confidence: 99%
“…Serial blood glucose curves at the hospital suffer from day to day variation in both diabetic dogs and cats; their repeatability, even when performed on consecutive days, is that low that may result in opposite recommendations for adjustment of insulin dose (Alt et al, 2007;Ford and Lynch, 2013). However, even at the home environment day to day variation is also expected, although it is less problematic in well regulated diabetic animals (Alt et al, 2007).…”
Section: Home Monitoring Of Blood Glucose Concentrations By the Ownermentioning
confidence: 99%